High Resolution Human Skin Image Segmentation by means of Fully Convolutional Neural Networks - Calderon-Delgado, Manuel; Tjiu, Jeng-Wei; Lin, Ming-Yi; Huang, Sheng-Lung (2018 International Conference on Numerical Simulation of Optoelectronic Devices (NUSOD), 2018)
Convolutional neural networks were applied to sub-micron-resolution optical coherence tomography images of the human skin for anatomical segmentation. The main layers of skin were discerned with an average 90% accuracy, which we believe to possess potential in the assessment of skin health.